Analysis of Science Process Skills for Grade 5 Elementary School Students on Science Materials during the Covid-19 Pandemic: Analisis Keterampilan Proses Sains Siswa Kelas 5 Sekolah Dasar pada Materi IPA dimasa Pandemi Covid-19 - Handayani, Evi; Setyawati, Enik (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to analyze the science process skills of grade 5 SDN Karangpuri 1 students based on the high, medium and low abilities of students in the science of animal movement organs during the covid-19 pandemic. This research method uses a descriptive qualitative approach. Data collection techniques using tests, interviews and documentation. The research was carried out at SDN Karangpuri 1 for 5th grade students. The subjects of this study were 3 students representing high, medium and low ability students. The results of data analysis show that, in online learning, the three students who represent the categories of high, medium and low ability students have science process skills in themselves, but need to be improved again because there are several aspects of science process skills that students lack. Keywords: Process Skills Science; Science Learning, Covid-19 Pandemic